Demographic Characteristics and Autopsy Findings by Origin of Deaths due to Firearm Injury: Analytical Research - Ekinci, Ecesu; Balcı, Yasemin; Çallak, Füsun; Anolay, Nurettin Nezih (The Bulletin of Legal Medicine, 2023)
Objective: Determining the origins of deaths due to gunshot wounds is an important problem in terms of forensic medicine. In this study, it was aimed to retrospectively examine the deaths due to gunshot wounds that were autopsied between 2013 and 2020.Method: Age, gender, place of death, type of weapon used, origin, entry area, number of entries, shooting distance, toxicological examination results were recorded and statistical analyzes were made.Results: 85.5% (n:218) of the cases were male, 14.5% (n:37) were female, and the rate of suicide and accidental injuries was higher in men than in women, and the rate of being a victim of homicide in women was higher than men (P
Keywords: Firearm, autopsy, murder, suicide, accident.